Polymeric Membrane Sensors for the Selective Determination of Metoclopramide Hydrochloride and their Applications to Pharmaceutical Analysis - A. Al-Haideri, Abdul-Muhsin; I. Abdulla, Najwa; K. Malih, Ibtihaj (Iraqi Journal of Pharmaceutical Sciences, 2017)
Metoclopramide (MCP) ion selective electrodes based on metoclopramide-phosphotungstic acid (MCP-PT) ion pair complex in PVC matrix membrane were constructed. The plasticizers used were tri-butyl phosphate (TBP), di-octyl phenyl phosphonate (DOPP), di-butyl phthalate (DBPH), di-octyl phthalate (DOP), di-butyl phosphate (DBP), bis 2-ethyl hexyl phosphate (BEHP). The sensors based on TBP, DOPP, DBPH and DOP display a fast, stable and linear response with slopes 59.9, 57.7, 57.4, 55.3 mV/decade respectively at pH ranged 2-6. The linear concentration range between 1.0×10-5 – 1.0×10-2 M with detection limit 3.0×10-6 and 4.0×10-6 M for electrodes using TBP, DOPP and DBPH while electrode using DOP shows a linear concentration range between 3.0×10-5 – 1.0×10-2 M and detection limit 6×10-6 M. The selectivity coefficient values were calculated for MCP with respect to different inorganic cations, sugars and amino acids using the MCP depending on TBP plasticizer which is also used for the determination of MCP in pure solutions and in pharmaceutical preparations by direct, standard addition methods and as an indicator electrode in potentiometric titration with phosphotungstic acid (PT) giving satisfactory results.Key words: Metoclopramide-HCl membrane sensors , Metoclopramide determination , pharmaceutical analysis , PVC membrane sensors